'Arriving At' Urban Policies: The Topological Spaces of Urban Policy Mobility. (14th September 2015) - Robinson, Jennifer
Abstract: Spatial vocabularies are stretched to their limits by the complexities of policy mobilities. Using the example of city‐wide strategic policymaking in Johannesburg, this essay argues for an enrichment of our vocabularies for appreciating how wider circuits of urban policy shape localized policy outcomes. Rather than tracing policies until they arrive somewhere, a more nuanced spatiality of policy mobility emerges when considering how policies are 'arrived at'. Thus policy influences can, for example, be ephemeral and recursive, international but already present in localities, have many simultaneous origins, and be folded into a relatively amorphous but specific policy blend. Drawing on John Allen's account of topological space, the essay indicates how both a more subtle spatiality and a more open politics of policy formation would emerge from turning the analysis of policy mobilities on its head in this way.